Sharia Microfinance Institutions' (SMIs) Resilience To Technological Disruption: Innovative Ecosystem Approaches On Lombok Island - Mas’ud, Riduan; Rifa'i, Khamdan; Fachrozi, Fachrozi; Fauzan, Fauzan (Jurnal Ekonomi, 2024)
This research explores the resilience of Sharia Microfinance Institutions (LKMS) on Lombok Island in facing the era of technological disruption. Using a qualitative approach with a case study method, this research focuses on technology adaptation and the implementation of an innovative ecosystem model that involves collaboration with fintech, educational institutions and local governments. The research results show that despite facing challenges such as limited technological infrastructure, high implementation costs, and resistance to change, LKMS in Lombok succeeded in increasing operational efficiency and expanding access to financial services through digital technology. Collaboration with fintech allows LKMS to access modern technology at more affordable costs, while collaboration with educational institutions and local governments helps increase literacy and public acceptance of digital services. This research concludes that innovation and collaboration are the keys to the success of LKMS in maintaining their relevance and positive contribution to financial inclusion and poverty alleviation in the digital era. These findings provide practical guidance for MFIs in other regions to adopt similar strategies to improve their operational resilience and effectiveness.